Growth, ionic homeostasis, and physiological responses of cotton under different salt and alkali stresses - Guo, Huijuan; Huang, Zhijie; Li, Meiqi; Hou, Zhenan (Scientific reports, 2020)
To better understand the mechanism of salt tolerance, we analyzed cotton growth and the ionomes in different tissues under different types of salt–alkali stress. Cotton was exposed to the soil salt and alkali stresses, NaCl, Na 2 SO 4 , and Na 2 CO 3 + NaHCO 3 , in a pot study. Salt and alkali stress significantly inhibited cotton growth, significantly reduced root length, surface area, and volume, and significantly increased relative electrical conductivity (REC) and malondialdehyde (MDA) content but also significantly increased antioxidant enzyme activities, and proline (Pro) content. The REC in leaves was higher under salt stress than under alkali stress, but the effects on Pro were in the order Na 2 CO 3 + NaHCO 3 > NaCl > Na 2 SO 4 . Principal component analysis showed a significant difference in ion composition under the different types of salt–alkali stress. Under the three types of salt–alkali stress, concentrations of Na and Mo increased significantly in different organs of cotton plants. Under NaCl stress, the absorption of Ca was inhibited, the transport capacity of P, Mg, and Cu was reduced, and the ion balance was maintained by promoting the uptake and transport of Zn, Mn, Al, and Mo. Under Na 2 SO 4 stress, the absorption of P and Ca was inhibited, the transport capacity of Mg, B, and Cu was reduced, and the ion balance was maintained by promoting the uptake and transport of S, Zn, Fe, Mo, Al, and Co. Under Na 2 CO 3 + NaHCO 3 stress, the absorption of P and S was inhibited, the transport capacity of Mg and B was reduced, but that of Al and Fe increased, and the ion balance was maintained by promoting the uptake and transport of Mn, Mo, Ni, and Co. The relative expression of GhSOS1 and GhNHX1 in leaves increased significantly under salt stress but decreased under alkali stress. These results suggest that cotton is well-adapted to salt–alkali stress via the antioxidant enzyme system, adjustment of osmotic substances, and reconstruction of ionic equilibrium; neutral salt stress primarily disrupts the ion balance, whereas alkali stress decreases the ability to regulate Na and inhibits the absorption of mineral elements, as well as disrupts the ion balance; and the changes in the expression of salt tolerance-related genes may partially explain the accumulation of Na ions in cotton under salt–alkali stress.